The Influence Of Innovative Work Behavior And Knowledge Management On Organizational Performance In Coffee Shops In Bandung City - Choiriyah Nurul Fadila; Agus Gunawan; Yoke Pribadi Kornarius; Angela Caroline (Publikasi Indonesia, 2023)
The proliferation of coffee shops in Bandung city is influenced by various factors, including the cultural significance of coffee consumption, the tendency of young individuals to frequent coffee establishments, and the influx of tourists to the city. Nevertheless, a considerable number of coffee shops have experienced closure shortly after their establishment due to their inability to sustain themselves in the industry. This predicament is often attributed to a deficiency in the knowledge required to manage human resources, thereby impeding organizational performance effectively. Consequently, this research aims to examine the impact of knowledge management and innovative work behavior on organizational performance. The study focuses on three coffee shops situated in Bandung, with a total sample size of 39 individuals. The findings from these establishments demonstrate a significant and positive influence of innovative work behavior and knowledge management on organizational performance. However, it is noteworthy that disparities in regulations and policies among the three coffee shops have engendered varying perspectives among employees regarding knowledge management, innovative work behavior, and organizational performance